Green production of metal nanoparticles for drug delivery applications - Aboeita, Nada Mostafa (AUC Knowledge Fountain, 2020)
Marine algae are a rich source of biologically active compounds such as sulfated polysaccharides, lipids, proteins, carotenoids and polyphenols, that can be used in food, cosmetic, nutraceutical and pharmaceutical industries due to their antioxidant, anticancer, antibacterial, and anticoagulant activities. In the present study, ultrasound-assisted extraction was performed on the red algae Pterocladia capillacea. The extraction procedure was optimized to maximize yield and total carbohydrate content. The extract was shown to possess potent antioxidant activity and was successfully used as a reducing and capping agent in the green synthesis of copper nanoparticles. The synthesized copper nanoparticles were characterized by UV-spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Transmission Electron Microscopy (TEM), and Dynamic Light Scattering (DLS). The produced nanoparticles constituted primarily CuO and they had an average size of 62.5 nm. FTIR spectra for the extract and copper nanoparticles synthesized from the algal extract showed characteristic peaks of polysaccharides. The synthesized copper nanoparticles were subsequently loaded with nedaplatin. UV data suggested that the mixture resulted in complex formation. Nedaplatin release profiles showed sustained release reaching a maximum at 120 h. The formulation was shown to have greater cytotoxic profiles relative to nedaplatin on hepatocellular carcinoma, breast cancer and ovarian cancer cell lines.